Perspectives of Double Feeding of the Melt Method on the Example of the Analysis of the InAs(1-x)–GaAs(x) Solid Solution Crystals Growth - Zahrabayova, Zaura; Kazimova, Vusala; Islamzade, Elnara; Alekperov, Akper (International Journal of Scientific Research and Management (IJSRM), 2022)
Using the example of  InAs-GaAs system, the potential of double feeding of the melt method for growing single crystals of semiconductor solid solutions is shown. The concentration profiles of InAs-GaAs solid solutions crystals for certain modes of the considered method are calculated in Pfann approximation. In addition, under the same conditions, InAs-GaAs crystals were grown and their concentration profiles were determined. The results obtained give good agreement between the experimental and calculated data. It is shown that mathematical modeling of InAs-GaAs crystals growth by setting the crystallization and melt-feeding rates with constituent components makes it possible to obtain the required distribution of the main components in the direction of crystal growth, including uniform distribution, in the entire series of continuous InAs-GaAs solid solutions. The double feeding of the melt method is shown to be promising for obtaining single crystals of semiconductor solid solutions with a given concentration profile.